SUBMONTANE PARAMESEȘ DEPRESSIONS IN THE STRUCTURAL CONTEXT OF THE TRANSYLVANIAN BASIN - I. A. IRIMUŞ; Corina BOGDAN (Studia Universitatis Babeş-Bolyai: Geographia, 2016)
Submontane Parameseș Depressions in the Structural Context of the Transylvanian Basin. The structure of the Alpine orogeny of the Silvania Mountains reveals fascinating and controversial Variscan remnants of the Hercynian orogeny. The Meseș hemi-anticline, incorporated into the alpine nappes structures of the Apusenides (Săndulescu, 1988) reflects the convulsions of the last thermo-tectonic Alpine cycle in a convergent geodynamic setting. The Meseș Mountains belong to an Alpine collisional chain of the Silvania Mountains, located in Northwestern Romania, as a wide V-shaped chain, detaching from the North Apuseni Mountains in the form of Variscan remnants.